Key to species of the genus Andixius Emeljanov & Hayashi (Hemiptera: Fulgoromorpha: Cixiidae) with descriptions of two new species - Wang, Xiaoya; Zhi, Yan; Chen, Xiangsheng (Zootaxa, 2020)
Two new species of the genus Andixius Emeljanov & Hayashi, A. cultratus Wang, Zhi & Chen, sp. nov. and A. lingulatus Wang, Zhi & Chen, sp. nov. are described and illustrated from China to provide the genus with six species in total. A key to species of Andixius is presented.